Examining the gender wealth gap in Germany - Eva M. Sierminska; Joachim R. Frick; Markus M. Grabka (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
Welfare-oriented analyses of economic outcome measures such as income and wealth generally rest on the assumption of pooled and equally shared resources among all household members. Yet the lack of individual-level data hampers the distribution of income and wealth within the household context. Based on unique individual-level wealth data from the German Socio-Economic Panel (SOEP), this paper challenges the implicit assumption of internal redistribution by considering an alternative definition of the aggregation unit and by controlling its effect on distribution and inequality analysis. We find empirical evidence for a significant gender wealth gap of about 30,000 euros in Germany, which amounts to almost 50,000 euros for married partners. Decomposition analyses reveal that this gap is mostly driven by differences in characteristics between men and women, the most important factor being the individual's own income and labor market experience, and particularly so at the bottom and top of the wealth distribution. However, this finding can only be shown with non-parametric decomposition techniques. Differences for those in the middle of the distribution appear to be mostly driven by the wealth function, i.e., the way in which women transform their characteristics into wealth.
Keywords: D13; D31; D69; I31; 330; Wealth gap; Wealth inequality; Gender; SOEP; Vermögensverteilung; Geschlechterdiskriminierung; Frauen; Schätzung; Deutschland